The philosophical and epistemological problem of cerebral death - Carrasco de Paula, Ignacio (Medicina e Morale, 1993)
The study starts with the observation of the divergence between two ways of understanding "cerebral death"; on one hand it is considered a new, more accurate and scientifically better definition of the death of the person; on the other hand a method for establishing the state of death of an individual. The author therefore analyses the two perspectives of death: the metaphisical and the biological. The object and the limits of the problem regarding the diagnosis of death: are then defined and the article concludes with an attempt to clarify some misunderstandings about this delicate question.